Fluoride emission rate analysis in proton exchange membrane water electrolyzer cells - Kuhnert, Eveline; Heidinger, Mathias; Bernroitner, Anna; Kiziltan, Özge; Berger, Erwin; Hacker, Viktor; Bodner, Merit (Frontiers in Energy Research, 2024)
The assessment of PEM water electrolyzer (PEMWE) degradation is essential for understanding their long-term durability and performance under real-world conditions. This research focuses on the fluoride emission rate (FER) as a crucial parameter during PEMWE operation. Two different FER analysis methods were evaluated, considering their feasibility and ease of integration into a PEMWE system. Various stressors were examined to gain insights into membrane degradation and explore potential mitigation strategies. The utilization of a photometric detection method allowed for the quantification of FER in each test. Results highlight a noteworthy correlation between applied stressors and FER, with variations depending on specific test conditions. An accelerated stress test conducted for 100 hours revealed a high FER at the anode of 0.83 μg h−1 cm−2 during the initial phase. Correspondingly, energy dispersive X-ray (EDX) mapping showed a reduction in Nafion™ content on the catalyst-coated membrane (CCM) surfaces, likely impacting proton conductivity and performance. Electrochemical results further support these findings, indicating performance changes corresponding to the observed membrane degradation.